An Empirical Study of the Impact of Mathematics Learning Engagement on Academic Performance in Sixth GradePrimary School Students - Sun, Jiayue; Pereira, Jerito (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2026)
This study aimed to explore the relationship between primary school students' mathematics learning engagement (including the three dimensions of vigor, dedication, and absorption) and their mathematics academic performance, and to analyze the differences in mathematics learning engagement among students of different genders, classes, and academic levels. The Chinese version of the Utrecht Work Engagement Scale for Students (UWES-S). was used to conduct a questionnaire survey among 96 students from two sixth-grade classes in a central primary school in a town. Data were analyzed using SPSS 24.0 for reliability analysis, correlation analysis, and independent samples t-test. Conclusion: Academic performance is a key factor influencing primary school students' mathematics learning engagement, the classroom environment may have a potential influence but did not reach statistical significance, and gender showed no significant effect. This study suggests that educators should seek to improve students' academic outcomes by enhancing their learning engagement.